Knowledge, Attitude and Practices of Dental Adhesives use among Dental Practitioners of Chitwan - Thakur, S N; Khanal, B; Chaulagain, R; Shrestha, P; Maharjan, A; Singh, H (Journal of Nepalese Prosthodontic Society, 2020)
Introduction: Denture adhesive (DA) is defined as a material used to adhere a denture to the oral mucosa. It plays an important role in the retention and the functional comfort among denture wearers. There are conflicting views in dentistry regarding the use of denture adhesives in clinical practice. Therefore, the main purpose of the study is to reveal the knowledge, attitude and practices regarding denture adhesives among the dental practitioners of Chitwan district, Nepal.Materials and Methods: A 20 item questionnaire was distributed among the registered dental practitioners of Chitwan districts using online google forms and the printed questionnaires were distributed personally to the practitioners who were accessible. Data were entered into Microsoft 2007 excel sheet and descriptive statistical analysis was done using SPSS version 20.Results: The results showed that 69.1% of General dental practitioners and 50% of other specialists had average knowledge while all the prosthodontics had good knowledge regarding denture adhesives. About 96.80% of General dental practitioners, 60% of other specialists frequently use denture adhesive in their practice. Only 20.2% of general dental practitioners and 20% of other specialists knew the adverse effects of zinc-containing denture adhesives. Most of the dental practitioners (93%) used powder form of denture adhesives.Conclusion: Most of the dental practitioners of Chitwan had fair knowledge, attitude and practice regarding denture adhesives.